Penalaran Analogi Siswa SMA Ditinjau dari Gaya Kognitif Reflektif Impulsif Dalam Menyelesaikan Masalah Open-ended - Fitroni, Wildan; Rosyidi, Abdul Haris (Universitas Negeri Surabaya, 2025)
This study aims to describe the analogical reasoning of senior high school students with reflective and impulsive cognitive styles, particularly those with high mathematical ability, in solving open-ended problems. Analogical reasoning ability is important for students' success in understanding and solving mathematical problems. This study uses a qualitative approach with high school students selected based on their reflective and impulsive cognitive styles and high mathematical ability. Data were collected through the Matching Familiar Figure Test (MFFT) adapted from Warli, an analogy reasoning test using open-ended problems from SPLTV material, and interviews. Data analysis was based on analogy reasoning indicators, including the structuring, mapping, applying, and verifying stages. The results of the study indicate that reflective and impulsive students with high mathematical ability, both of whom are female, are able to perform all four stages of analogical reasoning well, identify problem elements, map similarities, apply strategies, and verify their work accurately.